Aiming for middle-income country status: What are the growth options? - Breisinger, Clemens; Diao, Xinshen; Benin, Samuel; Thurlow, James; Kolavalli, Shashidhara (International Food Policy Research Institute, 2007)
It is almost certain that Ghana will become one of the few African countries to achieve the first Millennium Development Goal (MDG1) earlier than the target year of 2015. The country is also in a good position to sustain the 6 percent agricultural growth rate targeted by the Comprehensive Africa Agriculture Development Programme (CAADP). The Government of Ghana has also declared a more ambitious development goal of reaching middle-income (MIC) status by 2015. This brief summarizes the lessons learned from other countries and analyzes the growth and investment options needed in order for Ghana to reach its MIC goal.